Pre-sociology to the sociology of art - Alvarado Dávila, Víctor (2012)
Pre-sociology  to the sociology of artThe purpuse of this essay is to show a critical visión of the evolution of the sociological art, ranging from a pre-sociological phase to a strictly scientific one.My purpuse is to question the work of Heinich with the intention of knowing the traffic or the evolution of the method or the sociological point of view, in order to clarify the contributions of this discipline to the knowledge of the artistic phenomenon.